Clinical Effect of Poly Herbal Unani Formulation on Dyslipidemia- A Randomized Trial - Khairul Alam; Hasib Sheikh; Md. Abdus Samad (Turkish Journal of Agriculture: Food Science and Technology)
Background: In adults aged 30-70 with primary and moderate hyperlipidemia, the present study took place to investigate the therapeutic benefits of a polyherbal unani preparation called Garlitab. Methods: It was a prospective open label, herbal coded test drug-controlled, randomized trial. Out of total screened patients we were enrolled 212 hyperlipidemic patients of 30–70 years in the study fulfilling the inclusion criteria, we were recruited them from OPD of a hospital in Munshiganj and different Unani clinics of Dhaka, Bangladesh after obtaining written informed consent from the patients. Selected individuals were allocated into two groups at random. Group1 Received 500 mg Garlitab tablets twice daily and Group 2 received tablet atorvastatin calcium 10 mg 2 times daily. Height, weight, and blood pressure were recorded along with blood samples. The random distributions were carried out by a research assistant utilizing a random numbers table. Blood samples were taken at the beginning of the trial, 1.5 months later, and 3 months following the intervention. Results: Results for the test medication revealed a substantial drop in cholesterol levels between baseline and the data collected after three months and in case of male it was from 241.72±38.11 to 218.24±34.06 mg/dL for total cholesterol, from 198.27±30.57 to 173.54±29.34 mg/dL for LDL and from 280.78±85.81 to 207.07±51.40 mg/dL for triglyceride. HDL increases from 33.05±3.21 to 34.69±3.13 mg/dL in male patients. The control drug atorvastatin calcium also showed a significant decrease in lipids between baseline and after 3 months data and in case of male it was from 241.92±31.54 to 174.90±22.87 mg/dL for total cholesterol, from 196.20±30.91 to 130.30±24.29 mg/dL for LDL and from 279.48±115.35 to 141.27±59.55 mg/dL for triglyceride. It increases HDL from 32.00±2.25 to 34.03±2.19 mg/dL in male patients. Between the baseline and the 3-month data, the test medicine for females significantly reduced total cholesterol, LDL, and triglycerides and it was from 244.64±52.18 to 220.12±45.07 mg/dL, from 200.32±30.57 to 173.54±29.34 mg/dL and from 272.32±99.69 to 195.25±60.68 mg/dL respectively. HDL increases from 33.77±3.36 to 35.03±3.23 mg/dL. Between the baseline and the 3-month data, the control medication for females significantly reduced total cholesterol, LDL, and triglycerides and it was from 247.74±37.95 to 175.26±29.54 mg/dL, from 197.65±27.89 to 130.91±22.04 mg/dL and from 271.57±94.52 to 142.00±50.88 mg/dL respectively. It increases HDL from 32.22±2.32 to 33.46±2.94 mg/dL. Conclusions: According to the results of the study, the polyherbal formulation Garlitab can lower cholesterol levels. It may be a useful medication for treating primary hyperlipidemia.